Determinants of sexual activity and its relation to cervical cancer risk among South African Women - Williamson Anna-Lise; Denny Lynnette; Kelly Judy; Stander Ilse; Rosenberg Lynn; Carrara Henri; Hoffman Margaret; Cooper Diane; Shapiro Samuel (BMC, 2007)
Abstract Background Invasive cervical cancer is the commonest cause of cancer morbidity and mortality in South African women. This study provides information on adult women's sexual activity and cervical cancer risk in South Africa. Methods The data were derived from a case-control study of hormonal contraceptives and cervical cancer risk. Information on age of sexual debut and number of lifetime sexual partners was collected from 524 incident cases and 1541 hospital controls. Prevalence ratios and adjusted prevalence ratios were utilised to estimate risk in exposures considered common. Crude and adjusted relative risks were estimated where the outcome was uncommon, using multiple logistic regression analysis. Results The median age of sexual debut and number of sexual partners was 17 years and 2 respectively. Early sexual debut was associated with lower education, increased number of life time partners and alcohol use. Having a greater number of sexual partners was associated with younger sexual debut, being black, single, higher educational levels and alcohol use. The adjusted odds ratio for sexual debut < 16 years and ≥ 4 life-time sexual partners and cervical cancer risk were 1.6 (95% CI 1.2 - 2.2) and 1.7 (95% CI 1.2 - 2.2), respectively. Conclusion Lower socio-economic status, alcohol intake, and being single or black, appear to be determinants of increased sexual activity in South African women. Education had an ambiguous effect. As expected, cervical cancer risk is associated with increased sexual activity. Initiatives to encourage later commencement of sex, and limiting the number of sexual partners would have a favourable impact on risk of cancer of the cervix and other sexually transmitted infections